Notch4+ cancer stem‐like cells promote the metastatic and invasive ability of melanoma. Issue 8 (28th June 2016) - Lin, Xian; Sun, Baocun; Zhu, Dongwang; Zhao, Xiulan; Sun, Ran; Zhang, Yanhui; Zhang, Danfang; Dong, Xueyi; Gu, Qiang; Li, Yanlei; Liu, Fang
Abstract : Sphere formation in conditioned serum‐free culture medium supplemented with epidermal growth factor and basic fibroblast growth factor (tumorospheres) is considered useful for the enrichment of cancer stem‐like cells, also known as tumor‐initiating cells. We used a gene expression microarray to investigate the gene expression profile of melanoma cancer stem‐like cells (MCSLCs). The results showed that MCSLCs highly expressed the following Notch signaling pathway molecules: Notch3 (NM_008716), Notch4 (NM_010929), Dtx4 (NM_172442), and JAG2 (NM_010588). Immunofluorescence staining showed tumorosphere cells highly expressed Notch4. Notch4 high B16F10 cells were isolated by FACS, and Western blotting showed that high Notch4 expression is related to the expression of epithelial–mesenchymal transition (EMT)‐associated proteins. Reduced invasive and migratory properties concomitant with the downregulation of the EMT markers Twist1, vimentin, and VE‐cadherin and the overexpression of E‐cadherin was observed in human melanoma A375 and MUM‐2B cells. In these cells, Notch4 was also downregulated, both by Notch4 gene knockdown and by application of the γ‐secretase inhibitor, DAPT. Mechanistically, the re‐overexpression of Twist1 by the transfection of cells with a Twist1 expression plasmid led to an increase in VE‐cadherin expression and a decrease in E‐cadherin expression. Immunohistochemical analysis of 120 human melanoma tissues revealed a significant correlation between the high expression of Notch4 and the metastasis of melanoma. Taken together, our findings indicate that Notch4+ MCSLCs trigger EMT and promote the metastasis of melanoma cells. Abstract : We used an Agilent Gene Expression microarray to investigate the gene expression profile of melanoma cancer stem‐like cells and found high level of Notch4 expression is related to the cancer stem‐like cells. Then we explored the roles and mechanism of Notch4 by biological method and Immunohistochemistry in melanoma.